The Costs to the Nation of Inadequate Education: A Report Prepared for the Select Committee on Equal Educational Opportunity of the United States Senate - Levin, Henry M. (1972)
The purpose of this study was to estimate the costs to the nation of the inadequate education of a substantial portion of the population, where an inadequate education for the latter third of the twentieth century was defined as an attainment of less than high school graduation. Using data from the Department of Commerce and other sources in conjunction with extensive research literature from the social sciences, this report obtained the following findings: (1) The failure to attain a minimum of high school completion among the population of males 24 to 34 years of age in 1969 was estimated to cost the nation 237 billion dollars in income over the lifetime of these men; and, 71 billion dollars in foregone government revenues; (2) In contrast, the probable costs of having provided a minimum of high school completion for this group of men was estimated to be about 40 billion dollars; (3) Welfare expenditures attributable to inadequate education are estimated to be about three billion dollars each year and are probably increasing over time; and, (4) The costs to the nation of crime that is related to inadequate education appears to be about three billion dollars a year and rising